In-situ solid-state battery and preparation method thereof

By loading agents and coating solid electrolytes on the septum of solid -state batteries, a uniform three -dimensional lithium ion channel is constructed to solve the problem of high resistance of solid -state battery interface, and improves the electrochemical performance and cycle life of the battery.

CN119029361BActive Publication Date: 2025-01-24SINOCAT ENVIRONMENTAL TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411528586.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-01-24
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Solid-state batteries have high interface resistance in interface problems, resulting in poor transmission of lithium ions, short battery cycle life, and poor usage stability and safety.

Method used

By loading the initiator on the separator material, the problem of uneven distribution of the polymer electrolyte is improved, and the solid electrolyte is coated on the separator to build a uniform three-dimensional lithium ion channel, disperse the uneven concentration of lithium ions on the surface of the negative electrode, and promote its uniform deposition. , inhibiting the growth of lithium dendrites.

Benefits of technology

A significant reduction of the interface resistance, improving the electrochemical performance and energy density of the battery, extending the cycle life of the battery, and enhancing the stability and safety of the use of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119029361B_ABST
    Figure CN119029361B_ABST
Patent Text Reader

Abstract

The present invention discloses an in-situ solid-state battery and a preparation method thereof, belonging to the technical field of lithium / sodium batteries. The in-situ solid-state battery preparation method comprises: preparing a solid electrolyte slurry; preparing an initiator solution A; preparing a polymerization monomer solution A; preparing an initiator solution B; preparing a polymerization monomer solution B; applying the prepared initiator solution A to the A surface of the diaphragm and drying; applying the prepared initiator solution B to the B surface of the diaphragm and drying; then applying the solid electrolyte slurry to the B surface of the diaphragm and drying to obtain a modified diaphragm; laminating the positive electrode sheet, the modified diaphragm and the negative electrode sheet in sequence, welding the tabs and pre-sealing to obtain a solid-state battery cell; injecting the polymerization monomer solution A and the polymerization monomer solution B into the solid-state battery cell, and polymerizing and standing to obtain the result after completion. The present invention improves the interface compatibility between the electrolyte and the electrode, and improves the battery performance and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium / sodium batteries, and in particular to an in-situ solid-state battery and a preparation method thereof. Background Art

[0002] Developing lithium batteries with higher energy density is an important means to alleviate resource shortages and improve the utilization rate of green energy. The revival of lithium metal is expected to raise the energy density of batteries to a new level, but the problems of short battery cycle life, poor stability and safety caused by the poor compatibility of liquid electrolytes with it are still key factors that plague its further development and application. Compared with most liquid electrolytes, solid electrolytes (SSEs) are considered to be strong candidates for matching lithium negative electrodes and building the next generation of high energy density batteries because of their advantages such as suitable ionic conductivity, good electrochemical stability, safety and mechanical stability.

[0003] One of the biggest challenges facing solid-state batteries is the interface problem, namely the different interface problems between SSE and the positive and negative electrodes. The SSE and the positive / negative electrode surfaces cannot be fully infiltrated like the liquid electrolyte and the electrode surfaces. There will be a certain gap between the interfaces, and the constructed interface will have a high interface resistance, which will hinder the effective transmission of lithium ions between the interfaces.

[0004] The interface contact between the solid electrolyte and the rough surface electrode is poor, and it cannot fully infiltrate the positive and negative electrode surfaces like the liquid electrolyte, resulting in many tiny gaps at the interface, which leads to a significant increase in the interface impedance of the constructed lithium-ion battery. At the same time, the reduction in the actual contact area between the electrolyte and the positive and negative electrodes leads to a significant increase in the current density of the real electrochemical reaction, which is easy to cause the growth of lithium dendrites and shorten the battery cycle life. The in-situ polymerization and curing process for preparing solid polymer batteries is used to solve the problems of polymer-based electrolyte / electrode interface contact and excessive thickness of polymer-based electrolytes. As a new polymer-based solid-state battery preparation process, the liquid precursor can be in-situ polymerized and cured into a polymer-based electrolyte inside the battery, so that the electrolyte and the electrode have better interface compatibility, and the controllable preparation of ultra-thin polymer-based electrolytes can be achieved, which significantly improves the electrochemical performance and energy density of the battery. However, the current in-situ polymerization also has the problem that the obtained polymer electrolyte is unevenly distributed on the pole piece, and has little effect on improving the interface contact. Therefore, based on this problem, the present invention is specially proposed. Summary of the invention

[0005] The purpose of the present invention is to provide an in-situ solid-state battery and a preparation method thereof. The preparation method aims to improve the interface performance between the SSE and the positive and negative electrodes by performing different modifications on both sides of the diaphragm, thereby improving the electrochemical performance of the battery. At the same time, the method can improve the problem of uneven distribution of polymer electrolytes by directly loading initiators on the diaphragm material. In addition, a solid electrolyte is added to construct a layer of uniform three-dimensional lithium ion channels. These lithium ion channels can effectively disperse the uneven concentration of lithium ions on the surface of the negative electrode, promote the uniform deposition of lithium ions on the surface of the negative electrode lithium metal, and effectively inhibit the growth of lithium dendrites.

[0006] The purpose of the present invention is mainly achieved through the following technical solutions: an in-situ solid-state battery preparation method, comprising the following steps:

[0007] S1 Preparation of raw materials

[0008] S11 Preparation of solid electrolyte slurry

[0009] A binder and an organic solvent in a mass ratio of 1:10-50 are mixed and dissolved and stirred evenly, and then 5-20%wt of an organic silicon surfactant is added and mixed evenly to obtain a mixed solution 1, and an inorganic solid electrolyte powder is added to the mixed solution 1 and ultrasonically dispersed to obtain the solid electrolyte slurry; wherein the mass ratio of the inorganic solid electrolyte powder to the mixed solution 1 is 1:10-50;

[0010] S12 Preparation of initiator solution A

[0011] Mix and dissolve an azo or peroxide initiator A and a polar solvent in a mass ratio of 0.01-5:70-90 and stir evenly to obtain the initiator solution A;

[0012] S13 Preparation of polymerization monomer solution A

[0013] 55-89.9 wt % of a polymerizable monomer, 10-40 wt % of a lithium salt and 0.1-5 wt % of a plasticizer are mixed and stirred until completely dissolved to obtain the polymerizable monomer solution A;

[0014] S14 Preparation of initiator solution B

[0015] 0.01-5 wt % of Lewis acid as initiator B is uniformly dissolved in 70-90 wt % of a polar solvent to obtain the initiator solution B;

[0016] S15 Preparation of polymerization monomer solution B

[0017] The polymerization monomer and the polar solvent are mixed in a volume ratio of 1:1-30 and stirred evenly, and then 10-30 wt % of lithium salt is added to dissolve in the mixed solution, and stirred evenly to obtain the polymerization monomer solution B;

[0018] S2: coating the prepared initiator solution A on the A surface of the diaphragm and drying it, with a coating thickness of 2-10µm; coating the prepared initiator solution B on the B surface of the diaphragm and drying it, with a coating thickness of 2-10µm; and then coating the solid electrolyte slurry on the B surface of the diaphragm and drying it, with a coating thickness of 2-5µm, to obtain a modified diaphragm;

[0019] S3 stacking the positive electrode sheet, the modified separator and the negative electrode sheet in order to form a soft-pack battery, and welding the tabs and pre-sealing them with an aluminum-plastic film to obtain a solid-state battery cell without cationic in-situ polymerization;

[0020] S4: injecting the polymerization monomer solution A and the polymerization monomer solution B into the solid-state battery cell, wherein the injection ratio of the polymerization monomer solution A and the polymerization monomer solution B is 2-6 g / Ah. After the injection is completed, polymerization is carried out at room temperature. After standing for 2-10 hours, a solid-state battery based on in-situ polymerization is obtained.

[0021] In the preparation method, the molar concentration of the initiator in the prepared initiator solution A and the initiator solution B is 5 to 50 mmol / L; the molar concentration of the lithium salt in the prepared polymerization monomer solution A and the polymerization monomer solution B is 0.1 to 2 mol / L.

[0022] In the preparation method, in step S11, the molar concentration of the organic solvent is 0.1-3 mol / L;

[0023] In the steps S12, S14 and S15, the molar concentration of the polar solvent is 0.1-3 mol / L;

[0024] The organic solvent is one or a combination of any two or more of acetone, N-methylpyrrolidone, dimethylformamide, dichloromethane or dimethyl sulfoxide;

[0025] The polar solvent is one of dimethyl carbonate, ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, and ethylene glycol dimethyl ether, or a combination of any two or more thereof.

[0026] In the preparation method, the organosilicon surfactant is one or a combination of any two or more of aminosilane, nanosilicon dioxide, and aminosilicone oil;

[0027] The chemical formula of the inorganic solid electrolyte powder is Li3M2X3O 12 ; Wherein, M=Al or Ga, X=Si or P.

[0028] In the preparation method, the polymerization monomer solution A contains:

[0029] The polymerizable monomer is one or a combination of any two or more of acrylates, carbonates containing unsaturated carbon-carbon double bonds, and ionic liquids containing unsaturated carbon-carbon double bonds;

[0030] The lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalateborate, or a combination of any two or more thereof.

[0031] In the preparation method, in step S12, the azo or peroxide initiator A is one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, dicumyl peroxide, or a combination of any two or more thereof.

[0032] In the preparation method, the polymerization monomer solution B contains:

[0033] The polymerization monomer is one of 1,3-dioxolane, tetrahydrofuran, ethylene oxide, trioxymethylene, or a combination of any two or more thereof;

[0034] The lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalateborate, or a combination of any two or more thereof.

[0035] In the preparation method, in step S14, the initiator B is one of aluminum trifluoromethanesulfonate, boron trifluoride etherate, phosphorus pentafluoride, phosphorus trifluoride, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate, or a combination of any two or more thereof.

[0036] In the preparation method, the material of the diaphragm is one or a combination of any two or more of polyolefin, ceramic-coated polyolefin, polyimide, polyethylene terephthalate, cellulose nonwoven, glass fiber, and polymer prepared by electrospinning.

[0037] At the same time, the present invention also discloses an in-situ solid-state battery based on the above preparation method. The in-situ solid-state battery is prepared by the above preparation method.

[0038] Compared with the prior art, the present invention has the following beneficial effects: the in-situ solid-state battery and preparation method thereof of the present invention can improve the problem of uneven distribution of polymer electrolyte by directly loading the initiator on the diaphragm material; a layer of uniform three-dimensional lithium ion channels is constructed by coating a layer of solid electrolyte on the diaphragm, and these lithium ion channels effectively disperse the lithium ions with uneven concentration on the surface of the negative electrode, promote the uniform deposition of lithium ions on the surface of the negative electrode lithium metal, and effectively inhibit the growth of lithium dendrites; the electrolyte polymerized by free radicals in situ is friendly to the interface of the positive electrode material, helps to construct an integrated structure, and can significantly reduce the interface resistance; through the process and material design of the two layers of different diaphragms, the negative electrode layer of the battery is facilitated to conduct lithium ions and provide mechanical support, while the interface compatibility between the electrolyte and the electrode is improved for the positive electrode layer of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] The drawings described herein are used to provide a further understanding of the embodiments of the present invention, constitute a part of this application, and do not constitute a limitation of the embodiments of the present invention. In the drawings:

[0040] Figure 1 A flow chart for inventing an in-situ solid-state battery preparation method;

[0041] Figure 2 Schematic diagram of the structure of the modified electrolyte in the in-situ solid state of the present invention;

[0042] Figure 3 The battery performance cycle diagram of the batteries prepared in Comparative Example 1 and Specific Examples 1, 2, 3 and 4. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention.

[0044] like Figure 1 , Figure 2 As shown, the first embodiment of the present invention provides an in-situ solid-state battery preparation method, comprising the following steps:

[0045] S1 Preparation of raw materials

[0046] S11 Preparation of solid electrolyte slurry

[0047] A binder and an organic solvent in a mass ratio of 1:10-50 are mixed and dissolved and stirred evenly, and then 5-20%wt of an organic silicon surfactant is added and mixed evenly to obtain a mixed solution 1, and an inorganic solid electrolyte powder is added to the mixed solution 1 and ultrasonically dispersed to obtain the solid electrolyte slurry; wherein the mass ratio of the inorganic solid electrolyte powder to the mixed solution 1 is 1:10-50.

[0048] In this step, the binder is polyvinylidene fluoride (PVDF).

[0049] In this step, the molar concentration of the organic solvent is 0.1-3 mol / L. In specific applications, the organic solvent is one of acetone solvent, N-methylpyrrolidone, dimethylformamide, dichloromethane or dimethyl sulfoxide, or a combination of any two or more thereof.

[0050] In this step, the organosilicon surfactant is one of aminosilane, nano-silicon dioxide, and aminosilicone oil, or a combination of any two or more thereof.

[0051] In this step, the chemical formula of the inorganic solid electrolyte powder is Li3M2X3O 12 ; Wherein, M = Al or Ga, X = Si or P. For example, the inorganic solid electrolyte powder may be LLZO, LLTO, LLZTO, etc. In specific applications, the inorganic solid electrolyte powder may also be a combination of multiple substances.

[0052] S12 Preparation of initiator solution A

[0053] An azo or peroxide initiator A and a polar solvent are mixed and dissolved in a mass ratio of 0.01-5:70-90 and stirred evenly to obtain the initiator solution A.

[0054] In this step, the azo or peroxide initiator A is one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, and diisopropylbenzene peroxide, or a combination of any two or more thereof.

[0055] In this step, the molar concentration of the polar solvent is 0.1-3 mol / L. In specific applications, the polar solvent is one of ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, and ethylene glycol dimethyl ether, or a combination of any two or more thereof.

[0056] In this step, the initiator molar concentration of the prepared initiator solution A is 5 to 50 mmol / L.

[0057] S13 Preparation of polymerization monomer solution A

[0058] 55-89.9 wt % of a polymerizable monomer, 10-40 wt % of a lithium salt and 0.1-5 wt % of a plasticizer are mixed and stirred until they are completely dissolved to obtain the polymerizable monomer solution A.

[0059] In this step, the polymerizable monomer is one or a combination of any two or more of acrylates, carbonates containing unsaturated carbon-carbon double bonds (C=C), and ionic liquids containing unsaturated carbon-carbon double bonds (C=C).

[0060] In this step, the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalate borate, or a combination of any two or more thereof.

[0061] In this step, the molar concentration of the lithium salt in the prepared polymerization monomer solution A is 0.1-2 mol / L.

[0062] In this step, the polymerizable monomer, lithium salt and plasticizer are mixed and magnetically stirred at room temperature until they are completely dissolved.

[0063] S14 Preparation of initiator solution B

[0064] 0.01-5 wt % of Lewis acid is taken as initiator B and uniformly dissolved in 70-90 wt % of polar solvent to obtain the initiator solution B.

[0065] In this step, the initiator B is one of aluminum trifluoromethanesulfonate, boron trifluoride ethyl ether, phosphorus pentafluoride, phosphorus trifluoride, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate, or a combination of any two or more thereof.

[0066] In this step, the molar concentration of the polar solvent is 0.1-3 mol / L. In specific applications, the polar solvent is one of ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, and ethylene glycol dimethyl ether, or a combination of any two or more thereof.

[0067] In this step, the initiator molar concentration of the prepared initiator solution B is 5 to 50 mmol / L.

[0068] S15 Preparation of polymerization monomer solution B

[0069] The polymerization monomer and the polar solvent are mixed in a volume ratio of 1:1-30 and stirred evenly, and then 10-30 wt % of lithium salt is added to dissolve in the mixed solution and stirred evenly to obtain the polymerization monomer solution B.

[0070] In this step, the polymerization monomer is one of 1,3-dioxolane, tetrahydrofuran, ethylene oxide, and trioxymethylene, or a combination of any two or more thereof;

[0071] In this step, the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethanesulfonate, lithium bistrifluoromethanesulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalate borate, or a combination of any two or more thereof;

[0072] In this step, the molar concentration of the polar solvent is 0.1-3 mol / L; in specific applications, the polar solvent is one of ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, ethylene ethylene carbonate, propylene carbonate, butylene carbonate, and ethylene glycol dimethyl ether, or a combination of any two or more thereof.

[0073] In this step, the molar concentration of the lithium salt in the prepared polymerization monomer solution B is 0.1-2 mol / L.

[0074] In this step, the polymerizable monomer, lithium salt and polar solvent are mixed and magnetically stirred at room temperature until they are completely dissolved.

[0075] S2: Apply the prepared initiator solution A to the A surface of the diaphragm and dry it, with a coating thickness of 2-10µm; apply the prepared initiator solution B to the B surface of the diaphragm and dry it, with a coating thickness of 2-10µm; then apply the solid electrolyte slurry to the B surface of the diaphragm and dry it, with a coating thickness of 2-5µm, to obtain a modified diaphragm.

[0076] In this step, the material of the diaphragm is one or a combination of any two or more of polyolefin, ceramic-coated polyolefin, polyimide, polyethylene terephthalate, cellulose nonwoven, glass fiber, and electrostatically spun polymer.

[0077] In specific applications, both the initiator solution A and the initiator solution B can be coated by a scraper, and the solid electrolyte slurry can be coated by gravure coating, and dried at 20-30° C. Specifically, the drying temperature can be 25° C.

[0078] S3 stacks the positive electrode sheets, modified separators and negative electrode sheets in sequence for soft-pack batteries, and performs tab welding and aluminum-plastic film pre-sealing to obtain solid-state battery cells without cationic in-situ polymerization.

[0079] S4: injecting the polymerization monomer solution A and the polymerization monomer solution B into the solid-state battery cell, wherein the injection ratio of the polymerization monomer solution A and the polymerization monomer solution B is 2-6 g / Ah. After the injection is completed, polymerization is carried out at room temperature. After standing for 2-10 hours, a solid-state battery based on in-situ polymerization is obtained.

[0080] The second embodiment of the present invention provides an in-situ solid-state battery, which is prepared by the above-mentioned preparation method.

[0081] In summary, the in-situ solid-state battery and its preparation method of the present invention can improve the problem of uneven distribution of polymer electrolyte by directly loading the initiator on the diaphragm material; by coating a layer of solid electrolyte on the diaphragm, a layer of uniform three-dimensional lithium ion channels is constructed, and these lithium ion channels effectively disperse the lithium ions with uneven concentration on the negative electrode surface, promote the uniform deposition of lithium ions on the negative electrode lithium metal surface, and effectively inhibit the growth of lithium dendrites; the electrolyte polymerized by free radicals in situ is friendly to the interface of the positive electrode material, helps to build an integrated structure, and can significantly reduce the interface resistance; through the process and material design of the two layers of different diaphragms, the negative electrode layer of the battery is facilitated to conduct lithium ions and provide mechanical support, while the interface compatibility between the electrolyte and the electrode is improved for the positive electrode layer of the battery.

[0082] Therefore, the in-situ solid-state battery prepared by the present invention regulates the oxidative decomposition of SSE and the carbonate materials and transition metals in the positive electrode at a certain voltage by performing different modifications on both sides of the diaphragm, and provides more metal ion transmission channels, while enhancing the stability of SSE and the negative electrode material, thereby alleviating the interface problems at different interfaces of the solid electrolyte, which has huge application scenarios in high energy density batteries and low-altitude economy.

[0083] The above is the entire content of the present invention regarding the in-situ solid-state battery and the preparation method thereof. For a better understanding and implementation thereof, the present invention will further explain and illustrate it in detail in combination with specific embodiments and comparative examples below. Specific embodiment 1:

[0085] An in-situ battery is prepared by the following steps:

[0086] Step 1: Prepare Initiator Solution A

[0087] An azo or peroxide initiator A and a polar solvent are mixed and dissolved in a mass ratio of 0.3:75 and stirred to obtain the initiator solution A; wherein the azo or peroxide initiator A is azobisisobutyronitrile (AIBN), and the polar solvent is dimethyl sulfoxide (DMSO);

[0088] Step 2: Preparation of polymerization monomer solution A

[0089] 55 wt% of a polymerizable monomer, 20 wt% of a lithium salt and 1.1 wt% of a plasticizer are mixed and stirred continuously at room temperature for 6 hours until they are completely dissolved, to obtain the polymerizable monomer solution A; wherein the polymerizable monomer is vinylene carbonate (VC), the lithium salt is lithium bistrifluoromethylsulfonyl imide LiTFSI (1M), and the plasticizer is ethoxylated trimethylolpropane triacrylate (ETPTA);

[0090] Step 3:

[0091] The initiator solution A was coated on both sides of the diaphragm with a scraper to a thickness of 2µm, and then dried at 25°C to obtain a modified diaphragm;

[0092] Step 4:

[0093] The positive electrode (LiNi 0.9 Co 0.05 Mn 0.05 O2), modified diaphragm and silicon-carbon pole piece are sequentially stacked for soft-pack battery, and the pole ears are welded and pre-sealed with aluminum-plastic film to obtain a solid-state battery cell without in-situ polymerization;

[0094] Step 5:

[0095] The polymerization monomer solution A obtained in step 2 is injected into the solid-state battery cell that has not been subjected to in-situ polymerization at an addition ratio of 4 g / Ah, and polymerization is carried out at room temperature. After standing for 8 hours, a solid-state battery based on in-situ polymerization is obtained. Specific embodiment 2:

[0097] An in-situ battery is prepared by the following steps:

[0098] Step 1: Prepare initiator solution B

[0099] 0.01 wt % of Lewis acid as initiator B is uniformly dissolved in 75 wt % of polar solvent to obtain the initiator solution B; wherein the Lewis acid is aluminum trifluoromethanesulfonate (Al(OfT)3), and the polar solvent is dimethyl sulfoxide (DMSO);

[0100] Step 2: Preparation of polymerization monomer solution B

[0101] 55 wt% of a polymerizable monomer, 20 wt% of a lithium salt and 1.1 wt% of a plasticizer are mixed and stirred continuously at room temperature for 6 hours until they are completely dissolved, to obtain the polymerizable monomer solution A; wherein the polymerizable monomer is vinylene carbonate (VC), the lithium salt is lithium bistrifluoromethylsulfonyl imide LiTFSI (1M), and the plasticizer is ethoxylated trimethylolpropane triacrylate (ETPTA);

[0102] Step 3:

[0103] The initiator solution B was coated on both sides of the diaphragm with a scraper to a thickness of 2µm, and then dried at 25°C to obtain a modified diaphragm;

[0104] Step 4:

[0105] The positive electrode (LiNi 0.9 Co 0.05 Mn 0.05 O2), modified diaphragm and silicon-carbon pole piece are sequentially stacked for soft-pack battery, and the pole ears are welded and pre-sealed with aluminum-plastic film to obtain a solid-state battery cell without in-situ polymerization;

[0106] Step 5:

[0107] The polymerization monomer solution B obtained in step 2 is injected into the solid-state battery cell that has not been subjected to in-situ polymerization at an addition ratio of 4 g / Ah, and polymerization is carried out at room temperature. After standing for 8 hours, a solid-state battery based on in-situ polymerization is obtained. Specific embodiment 3:

[0109] An in-situ battery is prepared by the following steps:

[0110] Step 1: Preparation of solid electrolyte slurry

[0111] A binder and an organic solvent in a mass ratio of 1:30 are mixed and dissolved and stirred evenly, and then 10%wt of an organosilicon surfactant is added and stirred at room temperature until the mixture is evenly mixed to obtain a mixed solution 1, and an inorganic solid electrolyte powder is added to the mixed solution 1 and ultrasonically dispersed for 0.5 h to obtain a uniform milky white slurry, which is the solid electrolyte slurry; wherein the mass ratio of the inorganic solid electrolyte powder to the mixed solution 1 is 1:20; wherein the binder is polyvinylidene fluoride (PVDF), the organic solvent is dimethylformamide (DMF), the organosilicon surfactant is nano-silicon dioxide (SiO2), and the inorganic solid electrolyte powder is lithium lanthanum zirconium oxide (LLZO);

[0112] Step 2: Prepare Initiator Solution B

[0113] 0.01 wt % of Lewis acid as initiator B is uniformly dissolved in 75 wt % of polar solvent to obtain the initiator solution B; wherein the Lewis acid is aluminum trifluoromethanesulfonate (Al(OfT)3), and the polar solvent is dimethylformamide (DMF);

[0114] Step 3: Preparation of polymerization monomer solution B

[0115] 55 wt% of a polymerizable monomer, 20 wt% of a lithium salt and 1.1 wt% of a plasticizer are mixed and stirred continuously at room temperature for 6 hours until they are completely dissolved, to obtain the polymerizable monomer solution A; wherein the polymerizable monomer is 1,3-dioxolane (DOL), the lithium salt is lithium bistrifluoromethylsulfonyl imide LiTFSI (1M), and the plasticizer is fluoroethylene carbonate (FEC);

[0116] Step 4:

[0117] The initiator solution B is coated on both sides of the diaphragm with a scraper to a coating thickness of 2 µm and then dried at 25°C, and then the solid electrolyte slurry is gravure coated on one side of the diaphragm to a coating thickness of 2 µm to obtain a modified diaphragm;

[0118] Step 5:

[0119] The positive electrode (LiNi 0.9 Co 0.05 Mn 0.05 O2), modified diaphragm and silicon-carbon pole piece are sequentially stacked for soft-pack battery, and the pole ears are welded and pre-sealed with aluminum-plastic film to obtain a solid-state battery cell without in-situ polymerization;

[0120] Step 6:

[0121] The polymerization monomer solution B obtained in step 2 is injected into the solid-state battery cell that has not been subjected to in-situ polymerization at an addition ratio of 4 g / Ah, and polymerization is carried out at room temperature. After standing for 8 hours, a solid-state battery based on in-situ polymerization is obtained. Specific embodiment 4:

[0123] An in-situ battery is prepared by the following steps:

[0124] Step 1: Preparation of solid electrolyte slurry

[0125] A binder and an organic solvent in a mass ratio of 1:30 are mixed and dissolved and stirred evenly, and then 10%wt of an organosilicon surfactant is added and stirred at room temperature until the mixture is evenly mixed to obtain a mixed solution 1, and an inorganic solid electrolyte powder is added to the mixed solution 1 and ultrasonically dispersed for 0.5 h to obtain a uniform milky white slurry, which is the solid electrolyte slurry; wherein the mass ratio of the inorganic solid electrolyte powder to the mixed solution 1 is 1:20; wherein the binder is polyvinylidene fluoride (PVDF), the organic solvent is dimethylformamide (DMF), the organosilicon surfactant is nano-silicon dioxide (SiO2), and the inorganic solid electrolyte powder is lithium lanthanum zirconium oxide (LLZO);

[0126] Step 2: Prepare Initiator Solution A

[0127] An azo or peroxide initiator A and a polar solvent are mixed and dissolved in a mass ratio of 0.3:75 and stirred to obtain the initiator solution A; wherein the initiator is azobisisobutyronitrile (AIBN) and the polar solvent is dimethyl sulfoxide (DMSO);

[0128] Step 3: Preparation of polymerization monomer solution A

[0129] 55 wt% of a polymerizable monomer, 20 wt% of a lithium salt and 1.1 wt% of a plasticizer are mixed and stirred continuously at room temperature for 6 hours until they are completely dissolved, to obtain the polymerizable monomer solution A; wherein the polymerizable monomer is vinylene carbonate (VC), the lithium salt is lithium bistrifluoromethylsulfonyl imide LiTFSI (1M), and the plasticizer is ethoxylated trimethylolpropane triacrylate (ETPTA);

[0130] Step 4: Prepare Initiator Solution B

[0131] 0.01 wt % of Lewis acid as initiator B is uniformly dissolved in 75 wt % of polar solvent to obtain the initiator solution B; wherein the Lewis acid is aluminum trifluoromethanesulfonate (Al(OfT)3), and the polar solvent is dimethylformamide (DMF);

[0132] Step 5: Preparation of polymerization monomer solution B

[0133] 55 wt% of a polymerizable monomer, 20 wt% of a lithium salt and 1.1 wt% of a plasticizer are mixed and stirred continuously at room temperature for 6 hours until they are completely dissolved, to obtain the polymerizable monomer solution A; wherein the polymerizable monomer is 1,3-dioxolane (DOL), the lithium salt is lithium bistrifluoromethylsulfonyl imide LiTFSI (1M), and the plasticizer is fluoroethylene carbonate (FEC);

[0134] Step 6:

[0135] The initiator solution A is coated on the surface A of the diaphragm with a scraper to a coating thickness of 2µm, and then dried at 25°C; the initiator solution B is then coated on the surface B of the diaphragm with a scraper to a coating thickness of 2µm, and then dried at 25°C; then the solid electrolyte slurry is continuously gravure coated on the surface B of the diaphragm to a coating thickness of 2µm, and then dried at 25°C to obtain a modified diaphragm;

[0136] Step 7:

[0137] The positive electrode (LiNi 0.9 Co 0.05 Mn 0.05 O2), modified diaphragm and silicon-carbon pole piece are sequentially stacked for soft-pack battery, and the pole ears are welded and pre-sealed with aluminum-plastic film to obtain a solid-state battery cell without in-situ polymerization;

[0138] Step 8:

[0139] The polymerization monomer solution A and the polymerization monomer solution B obtained in step 3 and step 5 were injected into a solid-state battery cell that had not been subjected to in-situ polymerization at an addition ratio of 4 g / Ah, and polymerization was carried out at room temperature. After standing for 8 hours, a solid-state battery based on in-situ polymerization was obtained.

[0140] Comparative Example:

[0141] In order to reflect the advantages of the in-situ polymerization solid-state battery prepared by the modified diaphragm material in this scheme over the conventional organic electrolyte, the in-situ polymerization liquid is replaced by the basic electrolyte 1M lithium hexafluorophosphate (LiPF6) + [diethyl carbonate (DEC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC)] (1:1:1), and the unmodified diaphragm is used. Compared with the above four embodiments, the preparation process of the initiator solution, the in-situ polymerization liquid, the solid electrolyte slurry and the diaphragm is omitted, that is, all the previous steps are omitted, and the comparative sample battery is prepared using the existing electrolyte and diaphragm: the positive electrode sheet (LiNi 0.9 Co 0.05 Mn 0.05 O2), polyolefin film (model Celgard 2400), and silicon-carbon negative electrode sheets are stacked in sequence for soft-pack batteries, and the tabs are welded and pre-sealed with aluminum-plastic film to obtain uninjected battery cells. Then, the basic electrolyte is injected into the solid-state battery cells at a ratio of 4g / Ah, and the comparison sample battery is prepared after standing for 12 hours.

[0142] Different from the specific examples 1-4, the comparative example 1 uses an electrolyte to prepare a solid-state battery. The comparative electrochemical performance comparison results between the comparative example and the specific examples 1-4 are shown in the following Table 1:

[0143]

[0144] Table 1: Ionic conductivity, electrochemical window and cycle performance of comparative example 1 and specific examples 1, 2, 3 and 4

[0145] at the same time, Figure 3 The battery performance cycle diagram of the battery prepared in Comparative Example 1 and Specific Examples 1, 2, 3 and 4 is shown in FIG. Figure 3 From Table 1, we can see that:

[0146] By comparing the ionic conductivity, electrochemical window and cycle performance of Comparative Example 1 with those of Specific Examples 1, 2, 3 and 4, it can be seen that the ionic conductivity, electrochemical window and cycle performance of the in-situ polymerization solid-state battery prepared by the modified diaphragm material are higher than those of the battery prepared by the untreated diaphragm. Compared with the conventional basic electrolyte, due to the in-situ polymerization, a polymer network is formed inside, and these polymer networks provide channels that are conducive to ion migration, and these channels can efficiently conduct ions, thereby greatly improving the ionic conductivity. At the same time, the formed high molecular polymer also has a higher decomposition voltage and a stronger cycle capacity. The ionic conductivity, electrochemical window and cycle performance of Specific Example 4 are higher than those of other embodiments because different modifications are made to the two sides of the diaphragm to form in-situ polymers that are friendly to the positive and negative electrode interfaces, respectively, to regulate the oxidation decomposition of SSE and the carbonate materials and transition metals in the positive electrode at a certain voltage, and to provide more metal ion transmission channels, while enhancing the stability of SSE and the negative electrode material, thereby improving the cycle capacity.

[0147] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. An in-situ solid-state battery preparation method, characterized in that: The following steps are involved: S1 Preparation of raw materials S11 Preparation of solid electrolyte slurry A binder and an organic solvent in a mass ratio of 1:10-50 are mixed and dissolved and stirred evenly, and then 5-20%wt of an organic silicon surfactant is added and mixed evenly to obtain a mixed solution 1, and an inorganic solid electrolyte powder is added to the mixed solution 1 and ultrasonically dispersed to obtain the solid electrolyte slurry; wherein the mass ratio of the inorganic solid electrolyte powder to the mixed solution 1 is 1:10-50; S12 Preparation of initiator solution A An azo or peroxide initiator A and a polar solvent are mixed and dissolved in a mass ratio of 0.01-5:70-90 and stirred to obtain the initiator solution A; the initiator molar concentration in the prepared initiator solution A is 5-50 mmol / L; S13 Preparation of polymerization monomer solution A 55-89.9 wt % of a polymerizable monomer, 10-40 wt % of a lithium salt and 0.1-5 wt % of a plasticizer are mixed and stirred until completely dissolved to obtain the polymerizable monomer solution A; In the polymerization monomer solution A, the polymerization monomer is one of acrylates, carbonates containing unsaturated carbon-carbon double bonds, and ionic liquids containing unsaturated carbon-carbon double bonds, or a combination of any two or more thereof; the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalate borate, or a combination of any two or more thereof; S14 Preparation of initiator solution B Taking Lewis acid as initiator B and uniformly dissolving it in a polar solvent to obtain the initiator solution B; the initiator molar concentration in the prepared initiator solution B is 5 to 50 mmol / L; S15 Preparation of polymerization monomer solution B The polymerization monomer and the polar solvent are mixed in a volume ratio of 1:1-30 and stirred evenly, and then 10-30 wt % of lithium salt is added to dissolve in the mixed solution, and stirred evenly to obtain the polymerization monomer solution B; In the polymerization monomer solution B, the polymerization monomer is one of 1,3-dioxolane, tetrahydrofuran, ethylene oxide, and trioxymethylene, or a combination of any two or more thereof; the lithium salt is one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium trifluoromethylsulfonate, lithium bistrifluoromethylsulfonyl imide, lithium bisfluorosulfonyl imide, lithium difluorooxalatoborate, and lithium bisoxalate borate, or a combination of any two or more thereof; S2: Apply the prepared initiator solution A to the A surface of the diaphragm and dry it, with a coating thickness of 2-10µm; apply the prepared initiator solution B to the B surface of the diaphragm and dry it, with a coating thickness of 2-10µm; Then, the solid electrolyte slurry is coated on the B surface of the diaphragm and dried to a coating thickness of 2 to 5 μm to obtain a modified diaphragm; S3 stacking the positive electrode sheet, the modified separator and the negative electrode sheet in order to form a soft-pack battery, and welding the tabs and pre-sealing them with an aluminum-plastic film to obtain a solid-state battery cell without cationic in-situ polymerization; S4: injecting the polymerization monomer solution A and the polymerization monomer solution B into the solid-state battery cell, wherein the injection ratio of the polymerization monomer solution A and the polymerization monomer solution B is 2-6 g / Ah. After the injection is completed, polymerization is carried out at room temperature. After standing for 2-10 hours, a solid-state battery based on in-situ polymerization is obtained.

2. The in-situ solid-state battery preparation method according to claim 1, characterized in that: The molar concentration of the lithium salt in the prepared polymerization monomer solution A and polymerization monomer solution B is 0.1-2 mol / L.

3. The in-situ solid-state battery preparation method according to claim 1, characterized in that: In the step S11, the molar concentration of the organic solvent is 0.1-3 mol / L; In the steps S12, S14 and S15, the molar concentration of the polar solvent is 0.1-3 mol / L; The organic solvent is one or a combination of any two or more of acetone, N-methylpyrrolidone, dimethylformamide, dichloromethane or dimethyl sulfoxide; The polar solvent is one of dimethyl carbonate, ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, vinylene carbonate, vinyl ethylene carbonate, propylene carbonate, butylene carbonate, and ethylene glycol dimethyl ether, or a combination of any two or more thereof.

4. The in-situ solid-state battery preparation method according to claim 1, characterized in that: The organosilicon surfactant is one or a combination of any two or more of aminosilane, nanosilicon dioxide, and aminosilicone oil; The chemical formula of the inorganic solid electrolyte powder is Li3M2X3O 12 ; Wherein, M=Al or Ga, X=Si or P.

5. The in-situ solid-state battery preparation method according to claim 1, characterized in that: In step S12, the azo or peroxide initiator A is one of azobisisobutyronitrile, azobisisoheptanenitrile, dibenzoyl peroxide, and dicumyl peroxide, or a combination of any two or more thereof.

6. The in-situ solid-state battery preparation method according to claim 1, characterized in that: In step S14, the initiator B is one of aluminum trifluoromethanesulfonate, boron trifluoride ethyl ether, phosphorus pentafluoride, phosphorus trifluoride, lithium hexafluorophosphate, lithium tetrafluoroborate, and lithium trifluoromethanesulfonate, or a combination of any two or more thereof.

7. The in-situ solid-state battery preparation method according to claim 1, characterized in that: The material of the diaphragm is one or a combination of any two or more of polyolefin, ceramic-coated polyolefin, polyimide, polyethylene terephthalate, cellulose nonwoven, glass fiber, and polymer prepared by electrostatic spinning.

8. An in-situ solid-state battery, characterized in that: The preparation method is described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Solid electrolyte, preparation method thereof and solid-state battery

    CN113258132A

  • High-safety electrode plate and preparation method and application thereof

    CN115911254A